PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. LNK DI PERKEBUNAN BUKITLAWANG - Wina Ayang Sari; Khadijah Nurani (CV. Adiba Aisha Amira, 2023)
This research was conducted to determine how much influence compensation and work motivation have on employee performance. This study uses a quantitative approach, the data used are primary and secondary data. The population in this study were employees of PT. LNK Perkebunan Bukit Lawang with a total sample of 63 using a data collection technique, namely distributing questionnaires. Data processing techniques using multiple linear regression analysis, validity test, reliability test, classical assumption test, T test, F test and the coefficient of determination. The results of the analysis carried out using SPSS 29.0 software resulted in an output analysis showing that it was significant that the variables of compensation (X1), work motivation (X2), and employee performance (Y), the results of multiple linear regression Y = 8.002 + 0.384 + 0.341 as evidenced by t test shows that the compensation variable has a significant influence on employee performance as indicated by the value of t count > t table 2.965> 1.670 so that H_a is accepted. In the work motivation variable with a t count > t table 3.341> 1.670 so that H_a is accepted. The f test shows that the variables of compensation and work motivation have a significant effect on employee performance with the value of f count > f table, namely 9.693 > 3.15. The R^2 value indicates that compensation and work motivation affect employee performance by 0.554 (55.4%). And the results of statistical testing of compensation and work motivation have a contribution of 55.4% which affects employee performance.